2013
DOI: 10.1002/wrcr.20302
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient export from catchments on forested landscapes reveals complex nonstationary and stationary climate signals

Abstract: [1] Headwater catchment hydrology and biogeochemistry are influenced by climate, including linear trends (nonstationary signals) and climate oscillations (stationary signals). We used an analytical framework to detect nonstationary and stationary signals in yearly time series of nutrient export [dissolved organic carbon (DOC), dissolved organic nitrogen (DON), nitrate (NO 3 À -N), and total dissolved phosphorus (TDP)] in forested headwater catchments with differential water loading and water storage potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Previous observations of the dynamics of DOC and NO 3 − (Bernal et al, 2005;Heffernan and Cohen, 2010;Halliday et al, 2012;Lutz et al, 2012;Worrall et al, 2015), however, have shown that their temporal dynamics may vary (Taylor and Townsend, 2010;Mengistu et al, 2013;Thomas et al, 2014). Therefore, a tool is required to investigate these different non-stationary dynamics.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observations of the dynamics of DOC and NO 3 − (Bernal et al, 2005;Heffernan and Cohen, 2010;Halliday et al, 2012;Lutz et al, 2012;Worrall et al, 2015), however, have shown that their temporal dynamics may vary (Taylor and Townsend, 2010;Mengistu et al, 2013;Thomas et al, 2014). Therefore, a tool is required to investigate these different non-stationary dynamics.…”
Section: Core Ideasmentioning
confidence: 99%
“…Wavelet transform coherence (WTC) analysis reveals correlations between two time series that are timescale specific. In the past, there were only a few studies that included DOC and NO 3 − (Kang and Lin, 2007;Rusjan and Mikoš, 2010) or water quality time series in general (Mengistu et al, 2013) in wavelet analysis. Generally, a spatial component was not included.…”
Section: Core Ideasmentioning
confidence: 99%
“…At short time scales (e.g., hydrologic events), terrestrial-aquatic transport within a catchment, which is often expressed through hysteretic patterns between runoff and DOC concentrations or DOM composition, can differ dramatically across the longitudinal continuum as a result of differences in source contributions and mixing (Pacific et al 2010). At longer time scales (e.g., years to decades), DOM export is influenced by climatic cycles (e.g., El Nino-Southern Oscillation) and trends (e.g., warming) (Mengistu et al 2013).…”
Section: The Importance Of Integrating Both Space and Time Into Concementioning
confidence: 99%
“…Additionally, riverine DOM is the product of many complex processes that produce, consume, and modify organic matter. These processes change over daily to decadal time scales and over space scales ranging from low-order streams to high-order rivers (Mengistu et al 2013). Unraveling these complex processes is key to improving our understanding of rivers and the many ecosystem services they provide.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the statistical properties (e.g. mean, variance and autocorrelation) of the data are stable with respect to time [25], such as climate oscillations [26]. In mathematics, stationary can be defined as follows, when the distribution of (xt 1 , .…”
Section: Time Series Forecastingmentioning
confidence: 99%